Spectrum of gluten-related disorders: consensus on new nomenclature and classification - Sapone, Anna; Bai, Julio C; Ciacci, Carolina; Dolinsek, Jernej; Green, Peter HR; Hadjivassiliou, Marios; Kaukinen, Katri; Rostami, Kamran; Sanders, David S; Schumann, Michael; Ullrich, Reiner; Villalta, Danilo; et al. (BMC medicine, 2012)
A decade ago celiac disease was considered extremely rare outside Europe and, therefore, was almost completely ignored by health care professionals. In only 10 years, key milestones have moved celiac disease from obscurity into the popular spotlight worldwide. Now we are observing another interesting phenomenon that is generating great confusion among health care professionals. The number of individuals embracing a gluten-free diet (GFD) appears much higher than the projected number of celiac disease patients, fueling a global market of gluten-free products approaching $2.5 billion (US) in global sales in 2010. This trend is supported by the notion that, along with celiac disease, other conditions related to the ingestion of gluten have emerged as health care concerns. This review will summarize our current knowledge about the three main forms of gluten reactions: allergic (wheat allergy), autoimmune (celiac disease, dermatitis herpetiformis and gluten ataxia) and possibly immune-mediated (gluten sensitivity), and also outline pathogenic, clinical and epidemiological differences and propose new nomenclature and classifications.